Influence of polycyclic aromatic hydrocarbon exposure on IVF: now is the time to focus on women. Issue 2 (August 2020) - Netter, Antoine; Siri, Elena; Tassitro, Virginie; Resseguier, Noémie; Beauval, Nicolas; Sari-Minodier, Irène; Courbiere, Blandine; Perrin, Jeanne
Abstract: Research question: Is polycyclic aromatic hydrocarbon (PAH) exposure associated with the reproductive outcomes of IVF treatment? Design: A prospective, small-scale monocentric cohort study of couples who underwent IVF treatment between January 2018 and June 2019. Both members of each couple answered a questionnaire on PAH exposure and provided urine samples to measure urinary 1-hydroxypyrene (1-OHP) the day before oocyte retrieval and semen collection for fertilization. To assess the specific PAH exposure of gamete cells, immunostaining was conducted on both spermatozoa and granulosa cells obtained during IVF with an anti-benzo(a)pyrene diol epoxide (BPDE) monoclonal antibody that recognizes BDPE-DNA adducts. To assess DNA damage, a comet assay on spermatozoa was conducted. The PAH exposure was compared between couples who had positive HCG and couples who had negative HCG on day 14 after embryo transfer. Results: Eighteen couples were included. The mean 1-OHP level in women whose HCG tests were positive ( n  = 6) was significantly lower than that in women with negative HCG tests (0.098 [0.042–0.170] versus 0.177 [0.067–0.812] μg/g creatinine; P  = 0.048). The presence of BPDE-DNA adducts in granulosa cells of women with a negative (29.7 [16.2–57.5] arbitrary units) or positive HCG test (20.3 [9.3–23.3] arbitrary units) were not significantly different ( P  = 0.092). The urinary 1-OHP levels of men and BPDE-DNA adducts in spermatozoa showed no differences between groups. Conclusions: This exploratory research should encourage further studies to determine the effect of women's exposure to PAHs on reproductive outcomes of IVF treatment.